2015
DOI: 10.1039/c5ta04092b
|View full text |Cite
|
Sign up to set email alerts
|

Water desalination concept using an ionic rectifier based on a polymer of intrinsic microporosity (PIM)

Abstract: We describe ion current rectification using a Polymer of Intrinsic Microporosity (PIM) based on Tröger's base (PIM-EA-TB). When deposited asymmetrically over one (or more) 20 mm diameter hole(s) in 6 mm thick poly(ethylene terephthalate) and investigated in a twocompartment electrochemical cell with acidified aqueous NaCl on both sides, novel ionic diode effects are observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 31 publications
0
52
0
Order By: Relevance
“…The membrane sample was always on the side of the working electrode. Schematic diagrams in Figure 2E and 2F tentatively (following a mechanism suggested in earlier work [11]) explain this behaviour at least qualitatively based on protonation of the amine sites in PIM-EA-TB (see structure in Figure 1) leading to mixed proton and chloride conductivity.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The membrane sample was always on the side of the working electrode. Schematic diagrams in Figure 2E and 2F tentatively (following a mechanism suggested in earlier work [11]) explain this behaviour at least qualitatively based on protonation of the amine sites in PIM-EA-TB (see structure in Figure 1) leading to mixed proton and chloride conductivity.…”
Section: Introductionmentioning
confidence: 93%
“…The potential for applications of these devices ranges from analytical nanofluidic tools [9], natural cell pore mimics [10], to energy harvesting systems, and ionic rectifiers for desalination [11].…”
Section: Introductionmentioning
confidence: 99%
“…These new types of materials offer opportunities for new technologies to emerge and both MOF and PIM materials, in contact to aqueous electrolytes, have been observed to allow nanofluidic current rectification, or “ionic diode” phenomena to occur. Interest in ionic diode devices originates from efforts to mimic natural nanopores and the development of single channel nanofluidics with potential for applications in desalination, energy harvesting, and in “iontronics”…”
Section: Figurementioning
confidence: 99%
“…Although primarily developed for applications in gas storage and separation, it has been shown that the intrinsic microporosity and excellent processability of PIMs also lead to new applications in water treatment and in electrochemistry . In this report the effects of PIM‐7 on electrochemical processes are studied at modified electrodes immersed in aqueous media.…”
Section: Introductionmentioning
confidence: 99%